ANALISIS KEPUASAN KONSUMEN UNTUK MENINGKATKAN VOLUME PENJUALAN KEDAI KOPI KALA SENJA - Cucu Sumartini, Lilis; Fajriany Ardining Tias, Dini (Jurnal E-Bis (Ekonomi-Bisnis), 2019)
The development of the coffee shop business is influenced by the socio-economic development of the community and lifestyle changes. This condition is spurring for the growth of coffee shops by carrying the concept of modernization in an effort to increase consumer satisfaction. The level of customer satisfaction can be measured using the instruments of tangible dimensions, reliability, responsiveness, assurance, and empathy. The level of satisfaction measurement is done by using a questionnaire and 5 dimensions of quality measurement. Consumer satisfaction is a large value of expectations so that consumers feel their needs are met. Achieving satisfaction by 81.40%. impact on increasing sales. A high level of customer satisfaction can increase sales volume by 41.9% and the following month it rises to 49.50%. The data shows that customer satisfaction is one of the factors that can increase sales volume.